2010
DOI: 10.5194/acp-10-10033-2010
|View full text |Cite
|
Sign up to set email alerts
|

Extreme events in total ozone over Arosa – Part 2: Fingerprints of atmospheric dynamics and chemistry and effects on mean values and long-term changes

Abstract: Abstract. In this study the frequency of days with extreme low (termed ELOs) and extreme high (termed EHOs) total ozone values and their influence on mean values and trends are analyzed for the world's longest total ozone record (Arosa, Switzerland). The results show (i) an increase in ELOs and (ii) a decrease in EHOs during the last decades and (iii) that the overall trend during the 1970s and 1980s in total ozone is strongly dominated by changes in these extreme events. After removing the extremes, the time … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
42
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 78 publications
(127 reference statements)
12
42
0
Order By: Relevance
“…Our AMM analysis finds a significant contribution of ENSO to Boulder (US) ozone variability for PC score 3 (where ozone is maximum), which is similar to the result of Rieder et al (2010) analysis that also found a positive contribution over the US region. Note that the contribution is significant only for Winter and Spring months.…”
Section: Figsupporting
confidence: 77%
See 3 more Smart Citations
“…Our AMM analysis finds a significant contribution of ENSO to Boulder (US) ozone variability for PC score 3 (where ozone is maximum), which is similar to the result of Rieder et al (2010) analysis that also found a positive contribution over the US region. Note that the contribution is significant only for Winter and Spring months.…”
Section: Figsupporting
confidence: 77%
“…Thirdly, we compare our analysis with the analysis of total ozone data in Rieder et al (2010) and Rieder et al (2013). Our AMM analysis finds a significant contribution of ENSO to Boulder (US) ozone variability for PC score 3 (where ozone is maximum), which is similar to the result of Rieder et al (2010) analysis that also found a positive contribution over the US region.…”
Section: Figsupporting
confidence: 73%
See 2 more Smart Citations
“…Finally ozone is affected negatively by high values of geopotential height at 500 hPa in southern midlatitudes and northern mid-to high latitudes. The importance of synoptic-scale meteorological variability in understanding extratropical total ozone column variability has long been recognized (e.g., Harris et al, 2008;Kiesewetter et al, 2010;Rieder et al, 2010).…”
Section: Discussionmentioning
confidence: 99%